Aplastic Anemia in Patients with New-Onset Pancytopenia - Zain Kaleem, Ayesha Rehman, Muhammad Aamir Rafique, Aiman Altaf, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of aplastic anemia in patients with new-onset pancytopenia Study Design: This was discripative cross-sectional study Place and Duration of Study: Our current research was conducted at Shaikh Zayed Hospital, Lahore from June 2021 to November 2021 Methods: The study comprised 220 patients who had peripheral blood smears and showed new onset pancytopenia. Participants had to sign an informed consent form, be at least 14 years old, and be of either sex to be eligible. Patients were interviewed and physically examined for 20 to 30 minutes as part of the study, which included access to electronic health record data. Results: There were 122 (55.5%) male and 98 (44.5%) female patients in the study group. 107 (48.6%) patients belonged to middle class, 78 (35.5%) belonged to lower class while 35 (15.9%) patients belonged to high class. Aplastic anemia was diagnosed in 73 (33.2%) patients. Conclusion: The frequency of aplastic anemia was found to be 33.2% in children presenting with new-onset pancytopenia. There was no significant difference in the frequency of aplastic anemia across age, gender and socioeconomic status.